MINUM OBAT (PMO) TERHADAP KEPATUHAN MINUM OBAT PENDERITA TB PARU DI KECAMATAN MEDAN TELADAN KOTA MEDAN TAHUN 2013 - Nasution, Andreanda (HEARTY, 2014)
Lung Tuberculosis, caused by Mycobacterium tuberculosis, is a chronic disease, has long been widely known by people, and is feared because it is contagious. This disease becomes uncontrollable in some parts of the world and the main cause of death in Indonesia and in other developing countries. There were 918 people, with the prevalence of 45.9 per 100,000 inhabitants, who suffered from lung tuberculosis in Medan in 2010. The objective of the research was to analyze the influence of family’s social support (informational support, assessment support, instrumental support, and emotional support) as the taking medicine observers (PMO) on the compliance of taking medicine by Lung Tuberculosis patients in Medan Teladan Subdistrict, Medan, in 2013. The research was a survey with explanatory research type. The population was 45 taking medicine observers in the working area of Medan Teladan Puskesmas in the last six months, and all of them were used as the samples, using total sampling technique. The data were gathered by conducting interviews with questionnaires and analyzed by using multinomial logistic regression tests. The result of the research showed that there was the correlation between family’s social support (informational support, assessment support, instrumental support, and emotional support) as taking medicine observers (PMO) and the compliance of taking medicine by Lung Tuberculosis patients in Medan Teladan Subdistrict, Medan. The result of multiple logistic regression tests showed that there was the influence of informational support and assessment support (p<0.05) on the compliance of taking medicine by Lung Tuberculosis patients in Medan Teladan Subdistrict, Medan, and the most dominant variable was informational support. It is recommended that Medan Teladan Puskesmas should keep on educating (adherence) Lung Tuberculosis patients and PMO to comply with taking medicine in order to completely recovered from the illness and about the effect of the drop out incident. Medan Health Office should prioritize the competent PMO who are willing to monitor their family members in taking medicine regularly. The families of Lung Tuberculosis patients should pay full attention to the patients’ mental, physical, and social health by giving information to the patients so that they will recover from the illness soon and there will be no drop out incident.